Activation mechanisms of monocytes/macrophages in adult-onset Still disease - Tsuboi, Hiroto; Segawa, Seiji; Yagishita, Mizuki; Toko, Hirofumi; Honda, Fumika; Kitada, Ayako; Miki, Haruka; Ohyama, Ayako; Hagiwara, Shinya; Kondo, Yuya; Matsumoto, Isao; Sumida, Takayuki (Frontiers in Immunology, 2022)
Adult onset Still disease (AOSD) is a systemic inflammatory disorder characterized by skin rash, spiking fever, arthritis, sore throat, lymphadenopathy, and hepatosplenomegaly. Although the etiology of this disease has not been fully clarified, both innate and acquired immune responses could contribute to its pathogenesis. Hyperactivation of macrophages and neutrophils along with low activation of natural killer (NK) cells in innate immunity, as well as hyperactivation of Th1 and Th17 cells, whereas low activation of regulatory T cells (Tregs) in acquired immunity are involved in the pathogenic process of AOSD. In innate immunity, activation of monocytes/macrophages might play central roles in the development of AOSD and macrophage activation syndrome (MAS), a severe life-threating complication of AOSD. Regarding the activation mechanisms of monocytes/macrophages in AOSD, in addition to type II interferon (IFN) stimulation, several pathways have recently been identified, such as the pathogen-associated molecular patterns (PAMPs) and damage-associated molecular patterns (DAMPs)-pattern recognition receptors (PRRs) axis, and neutrophil extracellular traps (NETs)-DNA. These stimulations on monocytes/macrophages cause activation of the nucleotide-binding oligomerization domain, leucine-rich repeat, and pyrin domain (NLRP) 3 inflammasomes, which trigger capase-1 activation, resulting in conversion of pro-IL-1β and pro-IL-18 into mature forms. Thereafter, IL-1β and IL-18 produced by activated monocytes/macrophages contribute to various clinical features in AOSD. We identified placenta-specific 8 (PLAC8) as a specifically increased molecule in monocytes of active AOSD, which correlated with serum levels of CRP, ferritin, IL-1β, and IL-18. Interestingly, PLAC8 could suppress the synthesis of pro-IL-1β and pro-IL-18 via enhanced autophagy; thus, PLAC8 seems to be a regulatory molecule in AOSD. These findings for the activation mechanisms of monocytes/macrophages could shed light on the pathogenesis and development of a novel therapeutic strategy for AOSD.